Pengaruh Dana Pihak Ketiga (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) terhadap Likuiditas Bank Umum Syariah (BUS) Periode 2015-2017 - Utami, Mayvina Surya Mahardhika; Muslikhati, Muslikhati (Falah: Jurnal Ekonomi Syariah, 2019)
This research present to analyze the Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) to liquidity in Islamic Bank as a whole. The period used in this study is 2015 to 2017. This research type and uses an approach to not exist or not based on one or more variables. The variables in this research are Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF). While the dependent variable in this research is liquidity at Sharia Commercial Bank. The data used is secondary data from webside BI and OJK, while the data analysis technique is Multiple Regression Analysis. The results of this study indicate that the variable of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) simultaneously have a significant influence on the level of liquidity. While partially DPK and NPF have a significant influence, whereas CAR has no significant effect.